3
$\begingroup$

The question: consider a hole of radius a in a two-dimensional plane. We let the temperature on the hole's boundary be given by $f(\theta)$, where $\theta$ is a polar angle. From the temperature profile $T(r,\theta)$ for $r>a$, find the Poisson Integral Formula.

My solution: We know the general solution to Laplace's Equation in plane polars is

$$T(r,\theta)=C_0\ln(r)+D_0+\sum_{n=1}^{\infty}(A_n\cos(n\theta)+B_n\sin(n\theta))(C_nr^n+D_nr^{-n})$$

To make sure it doesn't blow up as $r\rightarrow \infty$, we make $C_0=0$ and $C_n=0$. Combining $A_n$ and $B_n$ with $D_n$ to get $Q_n$ and $W_n$, we get

$$T(r,\theta)=D_0+\sum_{n=1}^{\infty}r^{-n}(Q_n\cos(n\theta)+W_n\sin(n\theta))$$ We ntoe that these constants can be found using the boundary conditions, but are not important for my question.

Our formula above can be rewritten as $$T(r,\theta)=\sum_{n=0}^{\infty}\frac{C_n}{r^n}e^{in\theta}$$

For some constant $C_n$. Now, from here, how can I find the Poisson Integral Formula? I know the integral kernal is given by

$$P_r(\theta)=\sum_{n=-\infty}^{\infty}r^{|n|}e^{in\theta}$$

But I don't know how to go from there. Can anyone help me understand this?

Thank you in advance.

$\endgroup$
1
$\begingroup$

Here is how I did it:

We know that on the boundary of the hole $T(a, \theta) = f(\theta)$. Laplace's equation is $\frac{1}{r}\frac{\partial}{\partial r}\left(r\frac{\partial T}{\partial r}\right) + \frac{1}{r^2}\frac{\partial^2 T}{\partial\theta^2} = 0$. Let $T(r, \theta)$ be of the form $T = R(r)\Theta(\theta)$. $$ \frac{r}{R}\frac{\partial}{\partial r}\left( r\frac{\partial R}{\partial r}\right) = - \frac{\Theta''}{\Theta} = \lambda^2 $$ Since we have perfect thermal contact, our periodic boundary conditions are \begin{align} \Theta(-\pi) &= \Theta(\pi)\tag{1}\\ \Theta'(-\pi) &= \Theta'(\pi)\tag{2} \end{align} Suppose $\lambda = 0$. Then $\Theta(\theta) = a\theta + b$. Using equation (1), we have that \begin{gather*} \Theta(-\pi) = -a\pi + b = a\pi + b = \Theta(\pi)\\ 2a\pi = 0\Rightarrow a = 0 \end{gather*} When $\lambda = 0$, we have $\Theta(\theta) = b$. Additionally, we then have $\frac{r}{R}\frac{\partial}{\partial r}\left(r\frac{\partial R}{\partial r}\right) = 0$. Then $R(r) = \alpha\ln(r) + \beta$. Now suppose $\lambda\neq 0$. Our $\Theta$ equation is then that of a simple harmonic oscillator. $$ \Theta(\theta) = A\cos(\lambda\theta) + B\sin(\lambda\theta) \tag{3} $$ We can now use equations (1) and (2) on equation (3) to determine the eigenfunction of the solution to the Laplace equation. \begin{align*} \Theta(-\pi) &= \Theta(\pi)\\ 2B\sin(\lambda\pi) &= 0 \end{align*} Therefore, $B = 0$ or $\lambda = n\in\mathbb{Z} - \{0\}$. \begin{align*} \Theta'(-\pi) &= \Theta'(\pi)\\ 2A\lambda\sin(\lambda\pi) &= 0 \end{align*} Now we have that $A = 0$ or $\lambda = n\in\mathbb{Z} - \{0\}$. Since we aren't looking for the trivial solution, $\lambda = n\in\mathbb{Z} - \{0\}$. $$ \Theta_n(\theta) = A_n\cos(n\theta) + B_n\sin(n\theta) \tag{4} $$ Let's now look at the radial equation, $r^2R'' + rR' - n^2R = 0$, which is of the Cauchy-Euler type. Let $R = r^m$. Then we have $r^m\left[m(m - 1) + m - n^2\right] = 0$ so $m = \lvert n\rvert$. The general form of $T(r, \theta)$ is $$ T(r, \theta) = \alpha\ln(r) + \beta + \sum_{n = 1}^{\infty} \left(r^n + r^{-n}\right)\left(A_n\cos(n\theta) + B_n\sin(n\theta)\right). $$ Since $r$ goes out to infinity, $r^n$ and $\ln(r)$ would blow up at infinity. Therefore, $T(r, \theta)$ is of the form $$ T(r, \theta) = A_0 + \sum_{n = 1}^{\infty}\frac{A_n}{r^n}\cos(n\theta) + \frac{B_n}{r^n}\sin(n\theta). \tag{5} $$ To solve for the Fourier coefficients, we need to use the boundary condition on the hole of radius $a$. \begin{alignat*}{2} T(a, \theta) &= A_0 + \sum_{n = 1}^{\infty}\frac{A_n}{a^n}\cos(n\theta) + \frac{B_n}{a^n}\sin(n\theta) &&{} =f(\theta)\\ A_0 &= \frac{1}{2\pi}\int_{-\pi}^{\pi}f(\theta)d\theta \tag{6}\\ A_n &= \frac{a^n}{\pi}\int_{-\pi}^{\pi}f(\theta)\cos(n\theta)d\theta \tag{7}\\ B_n &= \frac{a^n}{\pi}\int_{-\pi}^{\pi}f(\theta)\sin(n\theta)d\theta \tag{8} \end{alignat*} To find the steady state temperature for $r > a$, we have equation (5) and equation (6) to (8) for the Fourier coefficients. We can also write equation (5) in terms of exponentials. $$ T(r, \theta) = \sum_{n = -\infty}^{\infty}\left(\frac{a}{r}\right)^n c_n\exp(in\theta) \tag{9} $$ where the Fourier coefficient is $$ c_n = \frac{1}{2\pi}\int_{-\pi}^{\pi}f(\varphi)\exp(-in\varphi)d\varphi. $$ Let's substitute $c_n$ in to equation (9). $$ \sum_{n = -\infty}^{\infty}\left(\frac{a}{r}\right)^n\left[ \frac{1}{2\pi}\int_{-\pi}^{\pi}f(\varphi)\exp(-in\varphi)d\varphi \right]\exp(in\theta) = \int_{-\pi}^{\pi}f(\varphi)\left[\frac{1}{2\pi} \sum_{n = -\infty}^{\infty}\left(\frac{a}{r}\right)^n \exp(in(\theta - \varphi))\right]d\varphi $$ where $\mathcal{P}(r, \theta - \varphi) = \frac{1}{2\pi}\sum\limits_{n = -\infty}^{\infty}\left(\frac{a}{r}\right)^n\exp(in(\theta - \varphi))$ is the Poisson kernel for $r > a$. We can write the Poisson kernel as $$ \mathcal{P}(r, \theta - \varphi) = \frac{1}{2\pi}\left[ \sum_{n = 0}^{\infty}\left(\frac{a}{r}\right)^n \exp(in(\theta - \varphi)) + \sum_{n = 1}^{\infty} \left(\frac{a}{r}\right)^n\exp(-in(\theta - \varphi))\right] $$ Let $z = \frac{a}{r}\exp(i(\theta - \varphi))$. Then the summations in our Poisson kernel are geometric series. That is, we can write the Poisson kernel as \begin{align*} \mathcal{P}(r, \theta - \varphi) &= \frac{1}{2\pi}\left[ \frac{1}{1 - z} + \frac{\bar{z}}{1 - \bar{z}}\right]\\ &= \frac{1}{2\pi}\frac{1 - z\bar{z}}{1 - (z + \bar{z}) + z\bar{z}} \end{align*} Note that $z\bar{z} = \frac{a^2}{r^2}$ and $z + \bar{z} = 2\frac{a}{r}\cos(\theta - \varphi)$. Let's multiple through by $r^2$ as we make the substitution. $$ = \frac{1}{2\pi}\frac{r^2 - a^2}{r^2 - 2ar\cos(\theta - \varphi) + a^2} $$ The solution to the Laplace steady state diffusion equation can be represented as $$ T(r, \theta) = \int_{-\pi}^{\pi}f(\varphi)\mathcal{P}(r, \theta)d\varphi. $$ Therefore, the Poisson Integral Formula for equation (5) is \begin{align*} T(r, \theta) &= \int_{-\pi}^{\pi}f(\varphi) \mathcal{P}(r, \theta - \varphi)d\varphi\\ &= \frac{1}{2\pi}\int_{-\pi}^{\pi} \frac{r^2 - a^2}{r^2 - 2ar\cos(\theta - \varphi) + a^2}f(\varphi)d\varphi \end{align*}

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.